2018
DOI: 10.1155/2018/4128984
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Angiogenic Alternative and Complementary Medicines for the Treatment of Endometriosis: A Review of Potential Molecular Mechanisms

Abstract: Endometriosis is caused by the growth or infiltration of endometrial tissues outside of the endometrium and myometrium. Symptoms include pain and infertility. Surgery and hormonal therapy are widely used in Western medicine for the treatment of endometriosis; however, the side effects associated with this practice include disease recurrence and menopause, which can severely influence quality of life. Angiogenesis is the main biological mechanism underlying the development of endometriosis. Numerous natural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 175 publications
0
25
0
Order By: Relevance
“…Endometriosis is characterized by chronic abdominal pain, infertility, dysmenorrhea, and sometimes anxiety, related to the degree of the pelvic pain [18,19]. This pathology is the result of interactions between various hormonal, immunological, and genetic factors, and it is characterized by an increased expression of inflammatory factors and angiogenesis [20].…”
Section: Endometriosis-an Inflammatory Diseasementioning
confidence: 99%
“…Endometriosis is characterized by chronic abdominal pain, infertility, dysmenorrhea, and sometimes anxiety, related to the degree of the pelvic pain [18,19]. This pathology is the result of interactions between various hormonal, immunological, and genetic factors, and it is characterized by an increased expression of inflammatory factors and angiogenesis [20].…”
Section: Endometriosis-an Inflammatory Diseasementioning
confidence: 99%
“…ey also showed that the same sample prevented the hepatic fat accumulation, although detailed underlying action mechanism on its inhibitory activity against hepatic fat accumulation was not extensively addressed [29]. Like AM, LE has also garnered much attention as a complementary herb that can act simultaneously on various targets in diseased states [31,32]. A study by Roh [33] reported that Gangjihwan, a polyherbal drug composed of LE as the main ingredient, demonstrated a beneficial effect in NAFLD mice via the regulation of the genes involved in lipid metabolism and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, andrographolide was proven to decrease endometriotic lesion volume and improve in generalized hyperalgesia in an endometriosis rat model. This effect was mediated via COX-2, tissue factor and the phosphorylation of p50 and p65 (Table 1 ) [116, 117].…”
Section: Experimental Studies On Medicinal Plants Against Endometriosismentioning
confidence: 99%
“…Diels root “dong quai” has been used in Chinese medicine to treat “blood stasis”. It has antispasmodic, analgesic, blood-enriching, blood circulating, and tonic effects, besides being an antioxidant, partly through the inhibition of anion radical formation [116]. A few studies have demonstrated its immunomodulatory and anti-inflammatory activities.…”
Section: Experimental Studies On Medicinal Plants Against Endometriosismentioning
confidence: 99%
See 1 more Smart Citation